(untitled) (International Journal of Food and Nutritional Sciences, 2023)
This research paper examines the impact of gender quotas on women’s political representation in Indian state legislatures. Using a mixed-methods approach, the study aims to evaluate the effectiveness of different types of gender quotas, including reserved seats for women and candidate quotas, in enhancing women’s participation and influence in politics. The research utilizes data from the National Election Data source and employs statistical analysis to assess the relationship between gender quotas and the percentage of women elected in various states and legislative bodies. The study also considers regional variations and the long-term sustainability of quota-driven increases in women’s representation. Key findings suggest that reserved seats for women consistently lead to higher percentages of women elected compared to general seats. Candidate quotas also play a significant role in increasing women’s participation in elections. Regional variations in the effectiveness of gender quotas highlight the importance of context-specific approaches, and the choice of legislative body impacts quota outcomes. The study reveals that gender quotas have a long-term impact, contributing to sustained improvements in women’s representation over time. State-level policies, such as gender quotas, are effective in enhancing women’s political engagement. Overall, this research provides valuable insights for policymakers and activists working towards gender equality in Indian politics. It contributes to a deeper understanding of the complex dynamics surrounding gender quotas and their role in shaping the political landscape in India.